Comparative Analysis of Automated Testing Tools (Automation Testing) Using Cypress and Selenium with Testng Framework on Web Portal Testing Performance in A Banking Company - Agam Aprianto; Gerry Firmansyah; Agung Mulyo Widodo; Habibullah Akbar (Green Publisher Indonesia, 2026)
The increasing complexity of web-based banking applications has intensified the need for efficient and reliable software testing methods to ensure system quality, security, and operational stability. Traditional manual testing often faces limitations in terms of execution speed, consistency, and scalability, making automated testing an essential approach in modern software development. This study aims to compare the performance of two widely used automated testing tools, Cypress and Selenium WebDriver integrated with the TestNG framework, in testing a banking web portal application. A quantitative experimental approach was employed by executing 104 automated test scenarios, consisting of 41 Login scenarios and 63 Customer Care scenarios, under identical testing conditions. The evaluation focused on execution time, test success rate, stability through repeated testing, and reporting capabilities. The findings reveal that both tools achieved a 100% test success rate across all scenarios. However, Cypress demonstrated significantly better performance in terms of execution efficiency, requiring only 511 seconds to complete all test cases, compared to 2,184 seconds required by Selenium WebDriver with TestNG. Repeated testing also confirmed the stability and consistency of Cypress results. In terms of reporting, Cypress provided a simpler and more user-friendly reporting mechanism, whereas Selenium TestNG with Allure offered more detailed analytical reporting features. In conclusion, Cypress is a more efficient automated testing solution for banking web portal applications, particularly when execution speed, ease of implementation, and testing productivity are prioritized.